2005
DOI: 10.1016/j.visres.2005.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of return is not a foraging facilitator in saccadic search and free viewing

Abstract: The ability to search and scan the environment effectively is a prerequisite for spatial behavior. A longstanding theory proposes that inhibition of previously attended loci (Inhibition of return; IOR) serves to facilitate exploration by increasing the likelihood to inspect new areas instead of returning to locations that have been inspected before. In this eye movement study we tested whether we could find evidence in favor of this hypothesis. Here we report that IOR does occur during search and free viewing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

32
110
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(147 citation statements)
references
References 27 publications
32
110
5
Order By: Relevance
“…Furthermore, no such evidence was found in the fine-grained analysis of fixation position focusing on letter position with a fixated word. These results are consistent with recent results from scene viewing and search suggesting that temporal O-IOR need not be accompanied by spatial O-IOR (Hooge et al, 2005;Smith & Henderson, 2009, 2011a. Although reading is a relatively young skill from the perspective of evolution, it appears to draw on much older systems developed for controlling the dynamic allocation of attention and eye movements.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, no such evidence was found in the fine-grained analysis of fixation position focusing on letter position with a fixated word. These results are consistent with recent results from scene viewing and search suggesting that temporal O-IOR need not be accompanied by spatial O-IOR (Hooge et al, 2005;Smith & Henderson, 2009, 2011a. Although reading is a relatively young skill from the perspective of evolution, it appears to draw on much older systems developed for controlling the dynamic allocation of attention and eye movements.…”
Section: Discussionsupporting
confidence: 90%
“…In this way, O-IOR could facilitate eye movement control by helping observers avoid reinspecting recently fixated locations (Klein, 1988;Klein & MacInnes, 1999). Evidence concerning this hypothesis is currently mixed, with several reports of equal or greater refixation of previously fixated locations in visual search and scene viewing (Hooge et al, 2005;Smith & Henderson, 2009, 2011a, 2011b. In the present study, little evidence for spatial consequences of O-IOR on fixation probability was observed.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Overt return of attention via eye movements has also been shown to experience delay (Klein & Hilchey 2011). Oculomotor IOR is thought to delay the programming of saccades to the previous fixation location (one back; Hooge, Over, van Wezel & Frens, 2005;Klein & MacInnes, 1999;MacInnes & Klein, 2003; and to the penultimate fixation location (two back; Dodd, Van der Stigchel & Hollingworth, 2009;Klein & MacInnes, 1999), and may even extend as far back as four fixations (four back; Dodd et al, 2009).…”
mentioning
confidence: 99%
“…A number of groups have questioned whether IOR is functional in influencing return probability during visual search (e.g., Hooge, Over, vanWenzel, & Frens, 2005;Smith & Henderson, 2009), while others have produced evidence for its effect in search and suggested that it may have an influence on up to the five most recently inspected items (Snyder & Kingstone, 2000), and that these effects may be graded, with the most recently fixated items having more inhibition (Boot, McCarley, Kramer, & Peterson, 2004). Wang, Zhang, and Klein (2010) suggested that IOR operates in static or slower dynamic search, whereas they did not observe it in faster, dynamic search.…”
mentioning
confidence: 99%